Management of Dystocia due to Monocephalus Twin Monster in a Graded Murrah Heifer by Caesarean Section - Periyannan, Mani; Selvaraju, Mani; Senthilkumar, Krishnamurthy; Varudharajan, Venkatraman; Prakash, Subramanian; Palanisamy, Mahakrishnan (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Monstrosity occurrences were associated with either infectious disease or congenital defects (Noakes et al., 2009). In bovines, 5-10% of dystocia cases are due to fetal developmental abnormality, which includes fetal monsters, fetal ascitis and fetal maldispositions (Batra et al., 2015) and 2.2 to 10% occurrence of all fetal anomalies in bovines are fetal twin monster (Ravikumar et al., 2012). Different varieties of twin monsters were reported earlier, and thoracophagus contributed 40%, omphalogus 35%, pyopagus 18%, cephalogus 2%, and ischiopagus 2% (Thangadurai and Selvaraju, 2015).